D. Luis da Cunha e os cristãos-novos portugueses - Alves, Paulo Renato de Castro (2010)
Portuguese diplomat at D. João V times, the first half of the XVIII century, D. Luis da Cunha represented the royalty as an ambassador in the English, Dutch and French royal courts. According to his two main works Instruções a Marco António de Azevedo Coutinho and Testamento Político, he was influenced by enlightenment ideas that were happening at the courts he has dealt with, he has constantly discussed the necessity of religious freedom in Portugal. It is not possible to describe part of Portugal Economical History without referring to the problem of the Judaism inside the territory. The diplomat realized that if the Portuguese monarchs intended to expel the Jews for religious reasons, they had to be concerned about the economic loss because of their leaving. Therefore, the nation interests were linked to religious interests, because time and spiritual powers were dose and far from each other. The diplomat instructions for the future monarch D. José 1 and to Marco António de Azevedo Coutinho were intended to recover the financial situation of the realm through the advance of the market production, the development of the market of sea items, the creation of a Company of Market and a"No Tax Zone" in Lisboa, that it would possible if there was the religious tolerance in Portugal, as D. Luis Cunha noticed that the new-Christians would be the most capable to do such economic transformations that were necessary to the realm development. The diplomat, trying to turn the country into a modern one, creates a theory based on the new-Christians defence, making sound critiques to the orders and catholic institutions as the Tribunal of the Holly 0ffice.